Diarrhea incidence in low- and middle-income countries in 1990 and 2010: a systematic review - Fischer Walker, Christa L; Perin, Jamie; Aryee, Martin J; Boschi-Pinto, Cynthia; Black, Robert E (BMC public health, 2012)
Background Diarrhea is recognized as a leading cause of morbidity and mortality among children under 5 years of age in low- and middle-income countries yet updated estimates of diarrhea incidence by age for these countries are greatly needed. We conducted a systematic literature review to identify cohort studies that sought to quantify diarrhea incidence among any age group of children 0-59 mo of age. Methods We used the Expectation-Maximization algorithm as a part of a two-stage regression model to handle diverse age data and overall incidence rate variation by study to generate country specific incidence rates for low- and middle-income countries for 1990 and 2010. We then calculated regional incidence rates and uncertainty ranges using the bootstrap method, and estimated the total number of episodes for children 0-59 mo of age in 1990 and 2010. Results We estimate that incidence has declined from 3.4 episodes/child year in 1990 to 2.9 episodes/child year in 2010. As was the case previously, incidence rates are highest among infants 6-11 mo of age; 4.5 episodes/child year in 2010. Among these 139 countries there were nearly 1.9 billion episodes of childhood diarrhea in 1990 and nearly 1.7 billion episodes in 2010. Conclusions Although our results indicate that diarrhea incidence rates may be declining slightly, the total burden on the health of each child due to multiple episodes per year is tremendous and additional funds are needed to improve both prevention and treatment practices in low- and middle-income countries.